RANCANGAN PENGUKUR SUHU TANPA KONTAK FISIK (NON-CONTACT) DAN PENGHALANG OTOMATIS BERBASIS ARDUINO DENGAN BAHASA PEMROGRAMAN C - Lingga Mudita Dharmawan; Rino Rino (bit-Tech, 2022)
Buddhi College Junior High School is one of the Buddhist schools in Tangerang City in the field of education that requires infrastructure in it. In the era of the Covid-19 pandemic which is increasingly rampant and many activities are dismissed so that it interferes with performance both in terms of education and in the business sector, until in the end many places have to be closed and even have to lose money due to this pandemic, then places must have standard protocols that are met . With this protocol, entrepreneurs and places, one of which is the world of education, need tools that can fulfill the protocol. The lack of knowledge about the symptoms of this disease requires the user to measure his body temperature when entering a place, one of which is a school or university. Temperature gauge is the hotness of an object or object that can be felt. not only used for companies or crowded places, temperature meters can also help health workers to monitor patients easily and quickly. Through the process of understanding until the design process is carried out, an Arduino-based tool design is formed with an algorithm with the c programming language and the workings of the tool to be made. The collected dataset is then sampled for manual processing. The manual process serves to measure the accuracy of the temperature being measured so that it can be implemented on the tool to be made.